Hadith #1031 - Sahih Muslim - Abu Salih (Sahih Muslim)
I narrate to you what I heard and saw from Abu Sa’id al-Khudri: One day I was with Abu Sa’id and he was saying prayer on Friday turning to a thing which concealed him from the people when a young man from Banu Mu’ait came there and he tried to pass in front of him; he turned him back by striking his chest. He looked about but finding no other way to pass except in front of Abu Sa’id, made a second attempt. He (Abu Sa’id) turned him away by Striking his chest more vigorously than the fi
Grade: Sahih

Hadith #3959 - Sahih Muslim - Abu Salih (Sahih Muslim)
I heard Abu Sa’id al-Khudri (Allah be pleased with him) said: Dinar (gold) for gold and dirham for dirham can be (exchanged) with equal for equal; but he who gives more or demands more in fact deals in interest. I sald to him: Ibn ‘Abbas (Allah be pleased with them) says otherwise, whereupon he said: I met Ibn ‘Abbas (Allah be pleased with them) and said: Do you see what you say; have you heard it from Allah’s Messenger (ﷺ), or found it in the Book of Allah, the Glorious and Majestic?
Grade: Sahih

Hadith #7108 - Sahih Muslim - Abu Salih (Sahih Muslim)
Allah’s Messenger (ﷺ) was in an (upper) apartment and we were standing lower to him and discussing (about the Last Hour). The rest of the hadith is the same, and Shu’ba said: I think he also said these words: The fire would descend along with them where they would land and where they would take rest (during midday (it would also cool down for a while). Shu’ba said: This hadith has been transmitted to me through Abu Tufail and Abu Sariha and none could trace it back directly to Allah’s
Grade: Sahih